Using liquid phase precursor method to create a high-efficiency Ca2SiO4:Eu2+ green-emitting phosphor - Phuc Dang Huu; Dieu An Nguyen Thi (Institute of Advanced Engineering and Science, 2022)
A standard solid-state reaction (SSR), a new fluid phase preparatory method utilizing LPP-SiO2(sol), and a water-based soluble silicone compound were employed to manufacture green Eu2+-based Ca2SiO4 phosphors liquid phase precursor (LPP-WSS). The generated phosphors feature large excitation spectra in the range of 225–450 nm and a strong green emission reaches the peak value at 502 nm owing to a 4f65d1→4f7(8S7/2) transition of Eu2+. These samples burned at 1100 1C produce the highest luminous intensity. The luminous properties of phosphors, which are manufactured by the liquid phase precursor LPP-WSS technique, were investigated at the range of 0.1-5.0 mol percent of Eu2+, with the maximum emission density observed at the value of 3.0 mol percent of Eu2+. The phosphors produced by the LPP-WSS technique exhibited a more uniform phase dispersion and higher luminous strength than those produced using the other procedures, according to a detailed report based on numerous characterizations. As a result, Ca2SiO4:Eu2+ has an indisputable possibility in white light-emitting diodes WLEDs and fluorescent lighting.